Intake of Lipid-based Nutrient Supplements during Illness and Convalescence among Moderately-underweight Malawian Childrenhomes (Journal of Health, Population and Nutrition, 2009)
doi:10.3329/jhpn.v26i4.1891 J Health Popul Nutr 2008 Dec:26(4):468-470